Bicolored display of Miconia albicans fruits: Evaluating visual and physiological functions of fruit colors - Camargo, Maria Gabriela G. de [UNESP]; Schaefer, H. Martin; Habermann, Gustavo [UNESP]; Cazetta, Eliana; Soares, Natalia Costa [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP] (Botanical Soc Amer Inc, 2015)
PREMISE OF THE STUDY: Most bird-dispersed fruits are green when unripe and become colored and conspicuous when ripe, signaling that fruits are ready to be consumed and dispersed. The color pattern for fruits of Miconia albicans (Melastomataceae), however, is the opposite, with reddish unripe and green ripe fruits. We (1) verified the maintenance over time of its bicolored display, (2) tested the communicative function of unripe fruits, (3) tested the photoprotective role of anthocyanins in unripe fruits, and (4) verified whether green ripe fruits can assimilate carbon. METHODS: Using a paired experiment, we tested whether detection of ripe fruits was higher on infructescences with unripe and ripe fruits compared with infructescences with only ripe fruits. We also measured and compared gas exchange, chlorophyll a fluorescence, and heat dissipation of covered (to prevent anthocyanin synthesis) and uncovered ripe and unripe fruits. KEY RESULTS: Although the bicolored display was maintained over time, unripe fruits had no influence on bird detection and removal of ripe fruits. Ripe and unripe fruits did not assimilate CO2, but they respired instead. CONCLUSIONS: Since the communicative function of unripe fruits was not confirmed, seed dispersers are unlikely to select the display with bicolored fruits. Because of the absence of photosynthetic activity in ripe and unripe fruits and enhanced photoprotective mechanisms in ripe fruits rather than in unripe fruits, we could not confirm the photoprotective role of anthocyanins in unripe fruits. As an alternative hypothesis, we suggest that the bicolored fruit display could be an adaptation to diversify seed dispersal vectors instead of restricting dispersal to birds and that anthocyanins in unripe fruits may have a defense role against pathogens.
Keywords: anthocyanin photoprotection; frugivory; fruit contrast; fruit phenology; fruit photosynthesis; Melastomataceae; Miconia albicans